1998
DOI: 10.7326/0003-4819-129-9-199811010-00007
|View full text |Cite
|
Sign up to set email alerts
|

Thiopurine Methyltransferase Genotype Predicts Therapy-Limiting Severe Toxicity from Azathioprine

Abstract: Analysis of thiopurine methyltransferase genotype is a quick way to identify patients at risk for acute toxicity from azathioprine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
183
3
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(196 citation statements)
references
References 13 publications
2
183
3
7
Order By: Relevance
“…Genetic polymorphisms in the thiopurine S-methyl transferase (TPMT) gene have been associated with decreased TPMT activity and the development of myelotoxicity due to high thioguanine metabolite concentrations. 3,4 Moreover, inosine triphosphate pyrophosphatase (ITPA) deficiency has recently been associated with AZA toxicity because of the accumulation of 6-thioinosine-triphosphate. 5,6 Theoretically, low TPMT activity might also augment the therapeutic efficacy of thiopurines and lead to better long-term clinical outcomes.…”
mentioning
confidence: 99%
“…Genetic polymorphisms in the thiopurine S-methyl transferase (TPMT) gene have been associated with decreased TPMT activity and the development of myelotoxicity due to high thioguanine metabolite concentrations. 3,4 Moreover, inosine triphosphate pyrophosphatase (ITPA) deficiency has recently been associated with AZA toxicity because of the accumulation of 6-thioinosine-triphosphate. 5,6 Theoretically, low TPMT activity might also augment the therapeutic efficacy of thiopurines and lead to better long-term clinical outcomes.…”
mentioning
confidence: 99%
“…It was discovered that several rare variants in the TPMT gene correlated with decreased activity; homozygous individuals suffered substantial haematopoietic toxicity (Krynetski et al, 1996). Recently, it has been reported that children with inactivating TPMT variants are at a greater risk for relapse, perhaps reflecting inadequate administration of thiopurines (Black et al, 1998). Pediatric leukaemia patients with TPMT variants, who receive cranial irradiation, have a greater likelihood for secondary brain tumours.…”
Section: Outcome and Snpsmentioning
confidence: 99%
“…Moreover, combination therapy is more effective than treatment with steroids [1,14,28] or 5-aminosalicylic acids (5-ASA) alone [29]. Also, the combination of thiopurines and oral cyclosporine has proven to be safe and effective for maintenance of intravenous cyclosporine-induced remission of severe steroid-refractory UC [30,31], though monotherapy with thiopurines may be sufficient [32].…”
Section: Efficacymentioning
confidence: 99%